250 labels used to stigmatise people with mental illness - Pinfold Vanessa; Thornicroft Graham; Rose Diana; Kassam Aliya (BMC, 2007)
Abstract Background The stigma against people with mental illness is a major barrier to help-seeking in young people for mental health problems. The objective of this study was to investigate the extent of stigma in relation to treatment avoidance in 14 year-old school students in England in relation to how they refer to people with mental illness. Methods This is a qualitative, cross-sectional study. The data were gathered as part of the baseline assessment for an intervention study intended to reduce stigma among 14 year old school students. The participating schools were two grammar (selective) schools and three comprehensive (non-selective) schools. At the start of the lesson, the students were asked 'What sorts of words or phrases might you use to describe someone who experiences mental health problems?' Words and terms used to refer to mental illness were enumerated. Using the grounded theory approach, words and terms were grouped in terms of their denotative and connotative meanings. Labels were then derived to capture the key themes attached by the students to the concepts of mental illness. The frequencies of occurrence for each word were also tabulated. Results 400 of the 472 participating students (85%) provided 250 words and terms to describe a person with mental illness. Five themes were identified from the data. The first theme called 'popular derogatory terms' (116 items) accounted for nearly half of the words examined. The second theme occurred less often and was described as 'negative emotional state' (61 items). The third theme demonstrated the confusion of young people between physical disabilities, learning difficulties and mental health problems (38 items). The use of psychiatric diagnoses (15 items) and terms related to violence (9 items) were unexpectedly uncommon. Conclusion Our findings suggest the hypothesis that help-seeking by mentally ill young people may be improved by interventions that address both their lack of factual information about mental illness, and those which reduce their strong negative emotional reactions towards people with mental illness.